2012
DOI: 10.1002/ptr.4828
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides Rb1 and Rd Regulate Proliferation of Mature Keratinocytes Through Induction of p63 Expression in Hair Follicles

Abstract: Ginsenosides Rb₁ and Rd are the two main types of ginsenosides in Panax ginseng and have been used as an additive to against alopecia. However, the mechanisms involved are largely unknown. To determine how ginsenosides prevent hair loss, we topically applied protopanaxadiol-type ginsenosides Rb₁ and Rd over the shaved skin of B57CL/6 mice, and monitored and assessed them for 35 days. We then investigated the effects of ginsenosides on cell genesis in different phases of adult hair follicles (HFs), using 5-brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…However, the potential applications for ginsenoside Rd in cosmeceuticals have been suggested in several previous papers [36,44,64]. Sung et al [36] demonstrated the wound healing effect of ginsenoside Rd using keratinocyte progenitor cells and human dermal fibroblasts, which was later confirmed by a laser burn wound model.…”
Section: Biological Activitiesmentioning
confidence: 94%
See 4 more Smart Citations
“…However, the potential applications for ginsenoside Rd in cosmeceuticals have been suggested in several previous papers [36,44,64]. Sung et al [36] demonstrated the wound healing effect of ginsenoside Rd using keratinocyte progenitor cells and human dermal fibroblasts, which was later confirmed by a laser burn wound model.…”
Section: Biological Activitiesmentioning
confidence: 94%
“…In a previous study, ginsenoside Rg3 induced the intrinsic apoptotic pathway in hepatocellular carcinoma (HCC) cells by altering apoptosis-related gene expression. In addition, it was observed Down-regulate the expression of p16, p21 and p53 [5,65] Hair loss prevention Induction of p63 expression [44] Rd Immune-suppression Reduce the CD4(?) and CD8(?)…”
Section: Biological Activitiesmentioning
confidence: 97%
See 3 more Smart Citations